Optic Nerve Sheath Diameter as a Bedside Assessment for Elevated Intracranial Pressure - Peter Williams (Case Reports in Critical Care)
A previously fit and healthy 26-year-old lady with no significant medical history presented with a two-month history of headaches. The headaches were prolonged, generalised, and unusually severe for the patient. Examination revealed papilloedema. The patient’s optic nerve sheath diameter was measured 3 mm posterior to the globe and found to be 7.5 mm. The patient subsequently had computed tomography scan of her brain that showed an optic nerve sheath diameter of 7.56 mm as measured 3 mm posterior to the globe. After an obstructive lesion was ruled out on the computed tomography scan, a lumbar puncture was then performed and cerebrospinal fluid was drained. An ultrasound of the optic nerve sheath diameter was repeated showing a reduced diameter of 5.6 mm. The patient was admitted to the neurology unit and ultimately diagnosed with idiopathic intracranial hypertension. This case report highlights the potential of rapidly identifying elevated intracranial pressure using a noninvasive method.